Criminal Liability of Perpetrators of Obstruction of Justice in Cases of Sexual Violence Crimes: Pertanggungjawaban Pidana terhadap Pelaku Obstruction of Justice dalam Perkara Tindak Pidana Kekerasan Seksual - Afifah, Yukiatiqa; Julianis, Dewi Yuslita (Universitas Islam Indonesia, 2023)
One of the causes of sexual violence is the failure of law enforcement officials to eradicate sexual predators due to acts of obstruction of justice which are often carried out by certain individuals. Obstruction of justice is an action that obstructs and obstructs the law enforcement process in various forms. This research will review the matter of how the obstruction of justice is regulated in Indonesian positive law and the forms of criminal liability for perpetrators of obstruction of justice in cases of criminal sexual violence? This research uses normative juridical methods in the form of a literature study and examines several statutory regulations. The results of his research indicate that regulations regarding obstruction of justice are contained in Article 221 of the Criminal Code and are spread across several special laws such as laws on eradicating corruption, terrorism and criminal acts of sexual violence. Regarding criminal liability, a person who commits obstruction of justice in a criminal case of sexual violence can be held accountable in the form of a maximum prison sentence of 5 years. Essentially, the regulations governing obstruction of justice in criminal acts of sexual violence are quite good, but the government is expected to immediately speed up the formation of derivative regulations or implementing regulations for the TPKS Law in the form of government regulations so that the TPKS Law can be implemented properly.Keywords: Criminal Liability, Obstruction Of Justice, Crime of Sexual Violence AbstrakSalah satu penyebab terjadinya kekerasan seksual adalah akibat gagalnya aparat penegak hukum dalam memberantas predator seksual dikarenakan adanya perbuatan obstruction of justice yang kerap kali dilakukan oleh oknum tertentu. Obstruction of justice merupakan tindakan yang merintangi dan menghalangi proses penegakan hukum dengan beragam bentuk. Penelitian ini akan mengulas bagaimana pengaturan obstruction of justice dalam hukum positif Indonesia dan bentuk pertanggungjawaban pidana terhadap pelaku obstruction of justice dalam perkara tindak pidana kekerasan seksual? Penelitian ini menggunakan metode yuridis normatif dalam bentuk studi kepustakaan dan mengkaji beberapa peraturan perundang-undangan. Hasil penelitiannya menunjukkan pengaturan mengenai obstruction of justice terdapat dalam Pasal 221 KUHP dan tersebar dalam beberapa undang-undang khusus seperti undang-undang pemberantasan korupsi, terorisme hingga tindak pidana kekerasan seksual. Mengenai pertanggungjawaban pidana, seseorang yang melakukan obstruction of justice dalam perkara tindak pidana kekerasan seksual dapat dimintai pertanggungjawaban dalam bentuk ancaman pidana penjara paling lama 5 tahun. Pada dasarnya pengaturan yang mengatur obstruction of justice dalam tindak pidana kekerasan seksual sudah cukup baik namun pemerintah diharapkan segera mempercepat pembentukan peraturan turunan atau aturan pelaksana dari UU TPKS dengan membentuk peraturan pemerintah (PP) sehingga UU TPKS tersebut dapat diimplementasikan dengan baik.Kata Kunci: Pertanggungjawaban Pidana, Obstruction Of Justice, Tindak Pidana Kekerasan Seksual